2002
DOI: 10.1016/s0920-5632(01)01760-1
|View full text |Cite
|
Sign up to set email alerts
|

Gauge potential singularities and the gluon condensate at finite temperatures

Abstract: The continuum limit of SU (2) lattice gauge theory is carefully investigated at zero and at finite temperatures. It is found that the continuum gauge field has singularities originating from center degrees of freedom being discovered in Landau gauge. Our numerical results show that the density of these singularities properly extrapolates to a non-vanishing continuum limit. The action density of the non-trivial Z2 links is tentatively identified with the gluon condensate. We find for temperatures larger than th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…[3] a slope of ∼ 0.2 GeV 3 was obtained for the SU(2) case which also is in qualitative agreement with our result. Notice that the lattice simulations of [24] observes a linear behavior of θ µµ , too. In Fig.…”
Section: Linear Growth Of θ µµmentioning
confidence: 87%
“…[3] a slope of ∼ 0.2 GeV 3 was obtained for the SU(2) case which also is in qualitative agreement with our result. Notice that the lattice simulations of [24] observes a linear behavior of θ µµ , too. In Fig.…”
Section: Linear Growth Of θ µµmentioning
confidence: 87%
“…We point out, however, that it is useful to disentangle the information carried by center elements and coset fields, defined above, when the vacuum energy is investigated. In particular, it was found that -in the continuum limit -the center elements provide a contribution to the gluon condensate [48,49].…”
Section: Gluon Field On the Latticementioning
confidence: 99%
“…3 For the set of initial values (a),(b), and (c) the axion field does not roll until t 0 , as indicated by the quantity w φ (t 0 ) ≃ −1. For point (d) φ in /M P is just above the threshold in (21) causing the field φ to roll at present: w φ (t 0 ) = −0.61. According to ref.…”
Section: (D) γ Interaction With Charged Leptons and Neutral Currentsmentioning
confidence: 94%
“…Neglecting the masses and interactions of the excitations, which is an excellent approximation at high temperatures as far as the excitation's equation of state is concerned, we have ρ − 3P ∝ T . In [21] the temperature dependence of the SU(2) gluon condensate was investigated on the lattice, and, indeed a linear rise of the gluon condensate with temperature was observed. Notice the conceptual and technical differences of [12] to the hard-thermal-loop (HTL) approach [22].…”
Section: Introductionmentioning
confidence: 96%